1993
DOI: 10.1055/s-2006-959980
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofHumulus lupulusExtract on the Central Nervous System in Mice

Abstract: Huinulus lupulus L. (hop) (Cannabidaceae) has been reported to have hypnotic and sedative effects (1-3). But there have been few recent reports concerning the detailed behavioral effects of the hop. Thus, we have investigated the CNS effects of Humulus lupulus (hop) extract using several behavioral tests, such as spontaneous locomotor activity, rotarod test, potentiation of pentobarbital-induced sleep, hypothermic, analgesic, and anticonvulsant tests in mice. Hop extracts (Emil Flachsmann AG) was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Reports have indicated that preparations of hops have sedative-like activity in frogs (Munch et al, 1933;Staven-Groenberg, 1928;Steidle, 1932), pigeons (Sikorski and Rusiecki, 1938), mice (Lee et al, 1993;Prokopenko et al, 1986), goldfish (Bouchardy, 1953), and golden carp (Grumbach and Mirimanoff, 1955). An understanding of the biochemical mechanism and the conclusive identification of compounds responsible for such activity have not yet been achieved.…”
Section: Sedative Activitymentioning
confidence: 99%
“…Reports have indicated that preparations of hops have sedative-like activity in frogs (Munch et al, 1933;Staven-Groenberg, 1928;Steidle, 1932), pigeons (Sikorski and Rusiecki, 1938), mice (Lee et al, 1993;Prokopenko et al, 1986), goldfish (Bouchardy, 1953), and golden carp (Grumbach and Mirimanoff, 1955). An understanding of the biochemical mechanism and the conclusive identification of compounds responsible for such activity have not yet been achieved.…”
Section: Sedative Activitymentioning
confidence: 99%
“…The authors observed a reduction in spontaneous motor activity related to the type of solvent used in the extraction procedure, being the etheric extract the most active in comparison with the aqueous and alcoholic ones. The effect of an hops extract on the CNS was evaluated in mice by Lee et al (1993): hypotermic, analgesic and anticonvulsant activities were observed in addition to sedative and hypnotic properties. A research group attributed the sedative effect of hops to 2-methyl-3-butene-2-ol, deriving from hop constituents during storage but probably also formed in vivo by metabolization of ␣-acids (Hänsel et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of the action of these components is to activate the neurotransmitter γ-aminobutyric acid (GABA) by modulating brain GABA(A) receptors (24), thus inhibiting the central nervous system. In particular, this effect of hops on the nervous system has been reported in animal model studies (11,21,44), it also has a narcotic effect of high concentrations of hop extract due to its aforementioned 2-methyl-3-buten-2-ol component (9,42). Basic research on hops has been used to help healthy stress free human population to sleep (31,38).…”
mentioning
confidence: 71%